Long-term survival of sorafenib-treated FLT3-ITD-positive acute myeloid leukaemia patients relapsing after allogeneic stem cell transplantation - Metzelder, Stephan; Dreger, Peter (European journal of cancer, 2017)
Background: Fms-like tyrosine kinase 3 internal tandem duplication (FLT3-ITD)-positive acute myeloid leukaemia (AML) relapsing after allogeneic stem cell transplantation (allo-SCT) has a dismal prognosis with limited therapeutic options. FLT3-ITD kinase inhibition is a reasonable but palliative experimental treatment alternative in this situation. Information on long-term outcome is not available. Methods: We performed a long-term follow-up analysis of a previously reported cohort of 29 FLT3-ITD-positive AML patients, which were treated in relapse after allo-SCT with sorafenib monotherapy. Findings: With a median follow-up of 7.5 years, 6 of 29 patients (21%) are still alive. Excluding one patient who received a second allo-SCT, five patients (17%) achieved sustained complete remissions with sorafenib. Four of these patients are in treatment-free remission for a median of 4.4 years. Interpretation: Sorafenib may enable cure of a proportion of very poor risk FLT3-ITD-positive AML relapsing after allo-SCT.
Gesehen am 29.10.2018